Overview of Knowledge About Covid - 19 in Pademawu Sub-District, Pamekasan Regency - Suryadi, Mohammad Shiddiq; Harista, Dessy Rindiyanti; Abdi, Akh. Choirul (Journal of Bionursing, 2025)
Background: Coronavirus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that attacks the respiratory tract. The disease caused by infection with this virus is called COVID-19. The main cause of people's non-compliance with health protocols is a lack of knowledge about the risks of disease and the benefits of treatment, as well as the main obstacles in accessing health services. Method: A cross-sectional design was used for the research design. There are 297 subjects in this study. The samples taken were 170 respondents. The sampling technique uses probabilistic sampling and random sampling techniques. The data collection method uses a questionnaire sheet. Use a statistical test with Spearman's rank test (a = 0.05). Results: Based on the results of the Knowledge Brief Research on COVID-19 in Sampan District, Sampan District, it is known that almost half of the community, namely 75 people (44.1%), do not have sufficient knowledge. The public is encouraged to educate themselves about COVID-19 and adhere to the COVID-19 health protocol. Conclussion: From the study it can be concluded that almost half of the community's knowledge is lacking in Pademawu Sub-District, Pamekasan Regency.